Antibiotic susceptibility, plasmid isolation and curing of some foodborne pathogens - Daniel, Ebakota; Osazee, Osarueme; Olisaka, Frances; Aibangbee, Jocelyn; GALAU, Panmwa; Osazee, Joseph (International Journal of Biological Research, 2016)
The indiscriminate use of antibiotics by individuals as well as in food production has been tagged one of the major reasons for the spread of antibiotic resistance in pathogens. Thus, there is a concern that foodborne bacteria may act as reservoirs of antibiotic resistance genes when distributed in large doses with food.Â This study aimed at determining the antibiotic susceptibility, plasmid isolation and curing of foodborne bacteria isolated from ready to eat (RTE) foods and salads in eating centers at the Benson Idahosa University, Benin City. Isolates were Enterobacter aerogenes, Escherichia coli, Staphylococcus aureus, Bacillus spp., Micrococcus sp. and Salmonella sp with S. aureus occurring most frequently. Total resistance to cefuroxime and augmentin as well as considerable resistance to ceftazidime and cefixime were observed in all isolates in antimicrobial susceptibility tests were done on Mueller-Hinton agar. Relative sensitivity to gentamicin, ofloxacin, nitrofurantoin and ciprofloxacin were observed. Plasmid profiling indicated that all isolates possess plasmids ranging from 100 bp to 1 kbp. Plasmid curing using sodium dodecyl sulfate (SDS) improved the sensitivity of isolates to antibiotics they were previously sensitive to but most isolates remained resistance to ceftazidime, cefuroxime, cefixime, and augmentin. This study shows that foodborne bacteria can possess and possibly transfer persistent antibiotic resistance plasmids thus calling for more caution in the use of antibiotics in food production and reduced antibiotics abuse. Further research is currently ongoing to cure the isolates of all plasmids and to elucidate how these plasmids are being transferred.